2009
DOI: 10.1002/ejoc.200900781
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Hybridisation of Water‐Soluble, Peptoid Nucleic Acid Oligomers Tagged with Thymine

Abstract: The preparation of a new class of backbone-modified PNA\ud mimetic incorporating thymine is described. Target dipeptoid\ud monomer 21 was synthesised from an N-[2-(thymin-1-yl)ethyl]\ud glycinate ester and a properly protected iminodiacetic\ud acid. The distinctive structural motif in the backbone is a\ud carboxy group, inserted to impart water solubility to the\ud oligomer. Two achiral oligopeptoid sequences (8-mer and 12-\ud mer), characterised by the shift of the amide carbonyl group\ud away from the nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The similar value was also used for DMF solution: ε (266 nm) = 17,500 dm 3 × mol −1 × cm −1 , ε (289 nm) = 5800 dm 3 × mol −1 × cm −1 and ε (300 nm) 7800 dm 3 × mol −1 × cm −1 [ 71 ]. In many studies only one ε coefficient (301 nm) 7800 dm 3 × mol −1 × cm −1 was used for the calculation of the loading of amino acids and other molecules on a resin [ 69 , 72 , 73 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…The similar value was also used for DMF solution: ε (266 nm) = 17,500 dm 3 × mol −1 × cm −1 , ε (289 nm) = 5800 dm 3 × mol −1 × cm −1 and ε (300 nm) 7800 dm 3 × mol −1 × cm −1 [ 71 ]. In many studies only one ε coefficient (301 nm) 7800 dm 3 × mol −1 × cm −1 was used for the calculation of the loading of amino acids and other molecules on a resin [ 69 , 72 , 73 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is also interesting to mention that, on the other hand, negatively charged nucleopeptoids carrying a poly(dT) sequence were not able to hybridize both poly(dA) and poly(rA). This proved that electrostatic interactions associated with adequate flexibility and three-dimensional presentation of the functional groups of the backbone provide determinant contributions for efficient RNA recognition [ 59 ]. Besides the RNA binding ability, many other interesting properties of the nucleobase-containing peptide-like molecules are known in the field of biomedicine, including the antigene activity and the modulation of the expression and function of noncoding RNAs [ 60 61 ].…”
Section: Reviewmentioning
confidence: 99%
“…In several research studies, it has been shown that various modifications of sugar phosphodiester linkage of nucleic acids can lead to oligonucleotide analogs with useful properties (Abramova et al 1991;Bell and Micklefield 2009;D'Alonzo et al 2011;D'Onofrio et al 2005;Zarra et al 2009;Zatsepin et al 2003). Interestingly, an extensive research work was conducted by many researchers on peptide-based analogs of nucleic acids (also referred to as nucleopeptides) which in some cases were characterized by a good intrinsic cell-membrane permeability as well as a significant ability to interact with natural nucleic acids leading to complexes of high thermal stability (Roviello et al 2010a).…”
Section: Introductionmentioning
confidence: 99%